Optimal reconfiguration of electrical distribution systems using mathematical programming - Borges, Marlon C. O. [UNESP]; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP] (Springer Nature, 2014)
This paper presents a novel mixed integer nonlinear programming (MINLP) model for the reconfiguration problem of electrical distribution systems (EDS), aiming to reduce the active power losses of the system. Two linearization techniques are applied in the MINLP model to obtain an equivalent mixed integer linear programming (MILP) model. The use of an MILP model guarantees convergence to optimality using existing optimization software. The proposed MILP model represents, with a suitable degree of accuracy, the steady-state operation of the EDS. Considering the typical operating conditions of the EDS, additional constraints are included in the proposed MILP model to reduce the computational effort demanded by its solution. The results of four test systems (33, 70, 136, and 417 nodes) are presented in order to show the accuracy as well as the efficiency of the proposed solution technique. © Brazilian Society for Automatics-SBA 2013.
Keywords: Active power losses reduction; Mixed integer linear programming; Reconfiguration of electric power distribution systems